POTENSI BIOCHAR SEKAM PADI TERHADAP PERUBAHAN PH, KTK, C ORGANIK DAN P TERSEDIA PADA TANAH SAWAH INCEPTISOL - Salawati Salawati; Muhammad Basir-cyio; Indrianto Kadekoh; Abd. Rahim Thaha (Universitas Tadulako, 2016)
One main constraint for growing wetland rice in Inceptisol is low soil fertility. Soil acidity (pH), CEC, C-organic are several indicators used to determine the level of soil fertility. To overcome these kinds of problems, such organic materials as rice husk biochar can be added to the soil in order to modify the soil chemical properties. This research compared treatments of different biochar rates with various fineness degrees on soil pH, CEC, C-organic, and available P. The research results showed that after incubation for 21 days at room temperature, the best interactionshown by the biochar at the rate of 15 ton ha-1 with 60 mesh particle size can reduce the soil pH by 5.19% from 7.7 to 7.3, increase the soil CECby 32.92% from 16.37 to 22.25 cmol (+) kg-1, improve the soil C-organic by 33.94% from 1.09% to 1.46%, and enhance the soil available phosphor by 277.08% from 12.61 ppm to 47.55 ppm.Keywords: Incubation, Rice HuskBiochar, and Soil Chemical Properties.